Measuring organizational attributes in primary care: a validation study in Germany - Ose, Dominik; Freund, Tobias; Kunz, Cornelia Ursula; Szecsenyi, Joachim; Natanzon, Iris; Trieschmann, Johanna; Wensing, Michel; Miksch, Antje (Journal of evaluation in clinical practice, 2010)
Objective Models for the structured delivery of care rely on organizational attributes of practice teams. The Survey of Organizational Attributes for Primary Care (SOAPC) is known to be a valid instrument to measure this aspect in the primary care setting. The aim of this study was to determine the validity of a translated and culturally adapted German version of the SOAPC. Methods The SOAPC was translated and culturally adapted according to established standards. The external validity of the German SOAPC was assessed using the German version of the Warr-Cook-Wall scale. A total of 200 practices randomly selected from a conference database were asked to participate in the validation study. Practice, clinicians and staff characteristics were determined via short-form questionnaires. We used standardized statistical procedures to reveal the psychometric properties of the SOAPC. Results A total of 54 practice teams participated by returning 297 completed questionnaires (297/425, response rate 69.8%). All four domains of the SOAPC (communication, decision making, stress/chaos, history of change) could be approved by factor analysis. Internal consistency is underlined by a Cronbach's alpha of 0.70 or higher in all categories. We show strong correlation with the Warr-Cook-Wall scale in all corresponding categories indexing high external validity. Conclusions The German SOAPC is a reliable and valid instrument for the assessment of organizational attributes of practice teams as the providers of quality of care. Moreover, the tool makes it possible to map the state of implementation of quality management and practice organization. The availability of the German SOAPC encourages further research on this topic in German-speaking countries.
Gesehen am 16.06.2023